Editorial Pointers. (Communications of the ACM, 2004)
This article presents information about the October 2004 issue of the journal "Communications of the ACM." A month from now one of the most contested U.S. presidential elections will be history. An unprecedented wave of electronic voting systems will replace traditional lever machines and chad-producing punch cards. As a result, tens of millions of U.S. citizens will cast their votes into computing systems on November 2, 2004. Venezuela is reeling from a presidential recall referendum in which election officials were suspected of rigging the nation's touch-screen voting machines in favor of the incumbent. The special section of this issue of the journal explores a variety of voting-related weaknesses and possible solutions from differing perspectives. Also in this issue, David Patterson traces the persistent imbalance between bandwidth and latency while detailing ways to cope with it. Phillip Armour insists the problems typically faced when developing computer software most often reflect what developers don't know.